Acculturation, Religious Coping, and Satisfaction with Life: A Quantitative Study on Foreign Students Living in Turkey - Sağır, Zeynep (Çanakkale Onsekiz Mart Üniversitesi, 2020)
The aim of this study was to illuminate the relationship between acculturation, religious coping, and degree of life satisfaction. The participants were 224 foreign students from 25 different countries where were studying Turkish. The data were collected in 2020 using survey methodology. The questionnaires included a Demographic Information Form, Bicultural Identity Integration Scale, Religious Coping Scale, and Satisfaction with Life Scale. The participants ranged in age from 18-40 years, with a mean age of 22.84; 65 were female, 159 were male. The results indicated that there was a significant relationship between positive religious coping (PRC) and cultural harmony. Also, there was a negative relationship between religious struggle and life satisfaction.

Bu çalışmanın amacı, kültürleşme, dini başa çıkma ve yaşam memnuniyeti arasındaki ilişkiyi ortaya koymaktır. Katılımcılar 25 farklı ülkeden Türkiye’ye gelmiş ve Türkçe eğitimi devam etmekte olan 224 yabancı öğrencidir. Veriler 2020’de anket tekniği kullanılarak toplanmıştır. Anket, Demografik Bilgi Formu, İki Kültürlü Kimlik Entegrasyonu Ölçeği, Dini Başa Çıkma Ölçeği ve Yaşam Memnuniyeti Ölçeğinden oluşmaktadır. 18-40 yaş aralığında, yaş ortalamasının 22.84 olduğu katılımcıların 65’i kadın ve 159’u erkektir. Sonuçlar, olumlu dini başa çıkma (ODBÇ) ve kültürel uyum arasında pozitif anlamlı bir ilişki olduğunu göstermiştir. Ayrıca dini çatışma ve yaşam memnuniyeti arasında ise negatif anlamlı bir ilişki bulunmuştur.
Kültürleşme, Dini Başa Çıkma ve Yaşam Memnuniyeti: Türkiye’de Yaşayan Yabancı Öğrenciler Üzerine Nicel Bir Araştırma
Keywords: Religious Studies; Din Araştırmaları; Religion; Society and Culture Studies; Din; Toplum ve Kültür Araştırmaları